Virtual Reality approaches for evacuation simulation of various disasters - Takeichi, Naohiro; Katagiri, Takeshi; Yoneda, Harumi; Inoue, Shusaku; Shintani, Yusuke (Collective Dynamics, 2020)
This paper presents a virtual reality (VR) system of evacuation in the cases of various disasters. We considered a combination of disasters under realistic scenarios. Disaster simulations by numerical models were imported into the VR system to express a realistic situation. Not only disaster experts but also designers and non-professionals are able to share realistic experiences for escape from the disasters. This system is useful for performance-based design, planning of escape, disaster prevention, evacuation drill etc. The VR system consists of Building Information Modelling, physical simulation models for disasters and human behaviour’s simulation.